2003
DOI: 10.1007/s11746-003-0805-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,3‐dicapryloyl‐2‐docosahexaenoylglycerol by a combination of nonselective and sn‐1,3‐selective lipase reactions

Abstract: A two-step consecutive synthetic method for the production of symmetrical, structured lipids by a combination of nonselective and sn-1,3 regioselective ester exchange reactions was investigated. In the first step, TAG with unspecifically substituted DHA were obtained by reacting tricapryloylglycerol (CCC) with ethyl docosahexanoate (EtDHA) using the lipase QLM (from Alcaligenes sp.), followed by removing the ethyl ester and CCC by molecular distillation. In the second step, sn-1,3 regioselective ester exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Two TAG regioisomers, which have the same FA composition and carry a functional FA at the 1(3)-and 2-position, are necessary in order to study this subject. The two regioisomers have been synthesized by transesterification of long-chain TAG (LLL) with medium-chain FA (MCFA) using a 1,3-position-specific lipase and by transesterification of medium-chain TAG (MMM) with long-chain FA (LCFA) (1)(2)(3)(4)(5)(6)(7)(8)(9). The products can reportedly be purified by HPLC (10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two TAG regioisomers, which have the same FA composition and carry a functional FA at the 1(3)-and 2-position, are necessary in order to study this subject. The two regioisomers have been synthesized by transesterification of long-chain TAG (LLL) with medium-chain FA (MCFA) using a 1,3-position-specific lipase and by transesterification of medium-chain TAG (MMM) with long-chain FA (LCFA) (1)(2)(3)(4)(5)(6)(7)(8)(9). The products can reportedly be purified by HPLC (10,11).…”
mentioning
confidence: 99%
“…Xu and colleagues (7,8) carried out large-scale preparation of TAG regioisomers by short-path distillation, but the resulting preparations were mixtures of MMM, MLM, and MLL because the distillation removed only FFA. Negishi et al (9) purified MLM from the reaction mixture, but the content of MLM was only 76%. For these reasons, a process for preparing larger amounts of pure TAG regioisomers (purity >90%) is strongly desired.…”
mentioning
confidence: 99%
“…60% of TAG-CLA with lipase RMP alone. Lipase QLM alone did not catalyze the esterification, producing only 3% TAG-CLA after 30 h. We speculate that the notable improvement obtained by using a blend of two lipases was due to the reactivity of these lipases (14). We also speculate that lipase QLM converted 1(3)-MAG and 1,3-DAG to 2-MAG and 1,2-DAG by interesterification.…”
Section: Resultsmentioning
confidence: 89%
“…Previously, we discussed the application of powdered lipase in interesterification reaction systems (12)(13)(14). We showed that it was possible to use powdered lipase in such reaction systems and to synthesize TAG consisting of mediumand long-chain FA, phytosterol esters, and structured lipids containing PUFA.…”
mentioning
confidence: 99%
See 1 more Smart Citation